Performatively speaking : speech and action in antebellum American literature - Rosenthal, Debra J., 1964- (University of Virginia Press, 2015)
In Performatively Speaking, Debra Rosenthal draws on speech act theory to open up the current critical conversation about antebellum American fiction and culture and to explore what happens when writers use words not just to represent action but to constitute action itself. Examining moments of discursive action in a range of canonical and noncanonical works T.S. Arthur's temperance tales, Fanny Fern's Ruth Hall, Nathaniel Hawthorne's The Scarlet Letter, Harriet Beecher Stowe's Uncle Tom's Cabin, and Herman Melville's Moby-Dick she shows how words act when writers no longer hold to a difference between writing and doing. The author investigates, for example, the voluntary self-binding nature of a promise, the formulaic but transformative temperance pledge, the power of Ruth Hall's signature or name on legal documents, the punitive hate speech of Hester Prynne's scarlet letter A, the prohibitory vodun hex of Simon Legree's slave Cassy, and Captain Ahab's injurious insults to second mate Stubb. Through her comparative methodology and historicist and feminist readings, Rosenthal asks readers to rethink the ways that speech and action intersect. -- Amazon.com.